Alterations in spontaneous delta and gamma activity might provide clues to detect changes induced by amyloid‐β administration. (9th February 2018) - Hidisoglu, Enis; Kantar‐Gok, Deniz; Er, Hakan; Acun, Alev Duygu; Yargicoglu, Piraye
Abstract: Alzheimer's disease (AD) is the most prevalent form of dementia and has an increasing incidence. The neuropathogenesis of AD is suggested to be a result of the accumulation of amyloid‐β (Aβ) peptides in the brain. To date, Aβ‐induced cognitive and neurophysiologic impairments have not been illuminated sufficiently. Therefore, we aimed to examine how spontaneous brain activities of rats changed by injection of increasing Aβ doses into the brain hemispheres, and whether these changes could be used as a new biomarker for the early diagnosis of the AD. Rats were randomized into following groups: sham (Sham) and seven Aβ‐treated (i.c.v.) groups in increasing concentrations (from Aβ‐1 to Aβ‐7). After recovery, EEG recordings were obtained from implanted electrodes from eight electrode locations, and then, spectral and statistical analyses were performed. A significant decrement in gamma activity was observed in all Aβ groups compared with the sham group. In delta activity, we observed significant changes from Aβ‐4 to Aβ‐7 group compared with sham group. Delta coherence values were decreased from Aβ‐4 to Aβ‐7 and Aβ‐5 to Aβ‐7 groups for frontal and temporal electrode pairs, respectively. A gradual increment was observed in Aβ1‐42 level till Aβ‐4 group. Positive correlation for global delta power and negative correlation for global gamma power between Aβ1‐42 peptide levels were detected. Consequently, it is conceivable to suggest gamma oscillation might be used to detect early stages of AD. Moreover, changes in delta activity provide information about the onset of major pathologic changes in the progress of AD. Abstract : This study focuses on dose‐dependent effects of Aβ peptide on brain activity in rats. Our findings demonstrate that less than Aβ peptide 20 µg in 5 µL cannot induce alterations in delta activity, whereas Aβ peptide doses, between 5 and 50 µg in 5 µL, have effect characterized by a reduction in gamma activity. Thus, delta activity changes may be thought to represent the major pathological stages of AD, while gamma activity changes may offer as a diagnostic biomarker for initial stages of AD.